Enhancing the Search Tool of the Android Settings through Natural Language Processing - Horita, Luiz Ricardo Takeshi; Paixão Júnior, Múcio Donizetti; Matos Júnior, João Batista Pereira (Anais Estendidos do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
Smartphones have become essential to daily life, providing much more than communication services. Continuously, the device is getting "smarter" and more complex with additional features and sensors. Configuring those features may not be so easy for new users, and making the Settings app easy to use is challenging. With this in mind, a search tool was indexed on its initial screen. However, it is still not efficient enough. While most Android search tools will try to match exactly the queried words, a more intuitive tool capable of finding content related to the meaning of those words would be desirably better. In this paper, we propose a solution based on word2vec model to encode the context of each screen in order to get more robust and intuitive search approach on the Android Settings application. Although the search problem has not been entirely solved yet, experiments showed satisfactory results, which include resolving more than 82% of cases that cannot be handled by the search tool embedded to the Android Settings